(untitled) (Research, Society and Development, 2020)
This study aimed to analyze whether the contents covered in undergraduate courses in health, education and law areas, from a Federal Higher Education Institution in Brazil, enable the training of students to deal with violence and sexual exploitation in professional practice. This is documentary research with teaching plans of six undergraduate courses, namely: Nursing, Physical Education, Medicine, Psychology, Pedagogy and Law. The project derived from this research was approved under CAAE register: 49775415.8.0000.5324. Twenty-four teaching plans were analyzed, according to the variables: discipline, course, workload, semester offered, and content covered. Only six plans include the theme of violence. We conclude that there is an urgent need for more significant commitment by universities in training and professional qualification regarding situations of violence against children and adolescents. The content referring to the legal obligation of the professional to identify, diagnose, notify and forward violence cases that reach children and adolescents assistance services, should be introduced already in academic education; however, this practice does not occur in most courses.